Global capital markets : a survey of legal and regulatory trends - Vasudev, P. M.; Watson, Susan, 1963- (Edward Elgar Publishing, 2017)
Capital markets are a continuous stream of activity and innovation. Constantly evolving and inherently dynamic, they give rise to complex regulatory and policy issues and offer rich material for analysis. Additionally, globalization has incentivized cross-border listings and international flows of capital. Global Capital Markets takes stock of recent trends and events by exploring their legal and regulatory implications across several jurisdictions from around the world. This book provides a critical analysis of current issues including investor activism, the challenges of cross-border regulatory enforcement and recent initiatives to empower shareholders to improve corporate governance. It also surveys longer-term trends such as the development of the nascent capital markets law in China over the last two decades and discusses the emerging issues from the increased use of dual class voting shares. Case studies draw on examples from nations such as the US, Canada, Europe, China, India and New Zealand. Timely and incisive, this book will appeal to students and academics in international corporate and securities law.